Driving Innovation in Data Analytics Adoption for Auditing in Tanzania's Banking Sector - Thomas Kwilasa; Daniel Ntabagi Koloseni (International Research Journal of Business Studies, 2025)
This study explores the factors affecting Data Analytics (DA) adoption in Tanzanian commercial banks' audit functions by expanding the Technology Acceptance Model (TAM) with Organisational Factors (OF) and Innovative Behaviour (IB). Using a quantitative approach, data were gathered from 193 internal auditors and analysed with SmartPLS through Partial Least Squares Structural Equation Modelling (PLS-SEM). The study found that perceived Usefulness, innovative behaviour, leadership support, Organisational culture, and technological infrastructure significantly influence DA adoption. Surprisingly, financial resources and regulatory compliance negatively affect adoption. Contrary to traditional TAM expectations, perceived ease of use and employee training do not have a significant impact. Practical implications indicate that banks should promote innovation, invest in infrastructure, and align regulatory frameworks with digital transformation objectives. Policymakers should create supportive environments, while practitioners must incorporate analytics into auditing workflows. Future research should examine longitudinal trends and cross-country comparisons, and provide qualitative insights into financial and regulatory challenges.